Serviço social na área sociojurídica: uma análise das requisições conservadoras que perpassam o debate sobre o depoimento especial - Ferreira, Adeilza Clímaco (2021)
Special Testimony is a technique of judicial listening aimed at cases of violence against children and adolescents that has gained relevance in Brazil and worldwide, with the participation of social workers for its execution. Therefore, the main objective of this doctoral dissertation is to analyze the conservative requirements that permeate the role of Social Service along with the Special Testimony. In order to achieve this objective, we outlined the following specific objectives: analyze the conservative perspectives which are present in protection policies aimed at children and adolescents who are victims of violence in Brazil; analyze the repercussions of social, political, and instrumental dimensions that permeate the Special Testimony for the ethical-political project of Social Service; analyze the fighting strategies of the Federal Council of Social Service (CFESS)/Regional Council of Social Service (CRESS) in dealing with judicial listening processes. We started from a qualitative approach anchored in a theoretical and methodological perspective based on historical and dialectical materialism. As a research technique, we used bibliographical and documental research and analysis. Our bibliographical research comprised studies of critical authors who develop their reflections on this theme; then, in the documental research, we carried out a study on laws, decrees, resolutions, reports, technical opinions, and news from the courts of justice. The interpretation of our research data showed us that the Special Testimony appears as a conservative requirement for Social Service, since the role of the interviewer proposed for the methodology implementation is not anchored in the list of professional attributions and competencies. Our analyses also revealed a tendency to return to the overvaluation of technicality resulting from the prevalence of the use of protocols in the search for material truth, to the detriment of the analysis of totality based on social studies of the phenomenon of violence. We identified that, despite the fighting strategies and resistance of the CFESS/CRESS group in defense of the ethical-political project and professional autonomy, the Brazilian judiciary has legitimized in the country a notion of positivist and conservative law based on criminal liability. The data also revealed that the tension caused by the CFESS/CRESS group has assumed a significant role in the defense of the Rights Guarantee System and, consequently, the full protection. Our analyses point to an institutional attempt by the courts of justice to relegate and subjugate professional knowledge, turning Social Service into an appendix in the solution of the needs of conservative justice, receding back as far as Law is concerned.